Democracy and Intra-Africa Trade - (:unkn) unknown (My University, 2023)
Despite numerous efforts by policymakers, trade among African countries remains abysmal. In this paper, we investigate whether democracy influences intra-Africa trade of goods. Using the gravity model on bilateral trade among 48 Sub-Sahara African countries over the period 2000 to 2018, we find that democracy fosters intra-Africa goods trade. This effect is more pronounced in the manufacturing sector. Reversals to autocracy, however, adversely impact intra-Africa trade flows. Our paper therefore highlights democratic development as an important channel for accelerating trade among African countries.
Keywords: African Research